Implementation of the Self Organized Learning Environment (SOLE) learning model at MTs bilingual sabilil khoir - Ifa Dwi Mahfudhoh; Risdiana Chandra Dhewy (Universitas PGRI Semarang, 2022)
Along with the development of education in Indonesia, teachers must prepare interesting learning strategies in order to facilitate the learning process and delivery of material to students. Not only teachers but students must also actively participate in the learning provided by the teacher. The SOLE learning model is a learning model created so that students can organize themselves into groups and learn to use smartphones connected to the internet with teacher guidance. The purpose of this study is to see the implementation of SOLE learning in terms of teacher activities, student activities, student learning outcomes, and student response questionnaires. This research is included in a quantitative descriptive study conducted at MTs Bilingual Sabilil Khoir in class VII-C with a total sample of 14 students. In the implementation of the SOLE learning model in this study, the results of teacher activities showed 3.25